2014
DOI: 10.1063/1.4900939
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigations of the mixing performance inside liquid slugs generated by a microfluidic T-junction

Abstract: Droplet-based microfluidics has gained extensive research interest as it overcomes several challenges confronted by conventional single-phase microfluidics. The mixing performance inside droplets/slugs is critical in many applications such as advanced material syntheses and in situ kinetic measurements. In order to understand the effects of operating conditions on the mixing performance inside liquid slugs generated by a microfluidic T-junction, we have adopted the volume of fluid method coupled with the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 58 publications
0
13
1
Order By: Relevance
“…S5). The failure of droplet formation for the contact angle of above 60° is different from the results of conventional droplets formation at T-junction where the droplets form even with the contact angle of 90° 108110 . This failure may be due to the high momentum of the Sheath phase at Re s > 1 which prevents the pressure build-up for overcoming surface tension forces.…”
Section: Resultscontrasting
confidence: 67%
“…S5). The failure of droplet formation for the contact angle of above 60° is different from the results of conventional droplets formation at T-junction where the droplets form even with the contact angle of 90° 108110 . This failure may be due to the high momentum of the Sheath phase at Re s > 1 which prevents the pressure build-up for overcoming surface tension forces.…”
Section: Resultscontrasting
confidence: 67%
“…The characteristic reaction time of the first reaction system of solute A can be described as t r = (k r C 0 A ) −1 . The characteristic diffusivity time is t d = L 2 /2D s,G [88]. In Sec.…”
Section: E Modeling Liquid-liquid Mass Transfer and Reaction In A Jamentioning
confidence: 98%
“…Wang, et al studied the cross-shaped microchannel in Figure 3 c. It is found that the IOS of the droplets generated in this channel has a low initial value [ 57 ]. Asymmetric dispersed phase inlets distribution [ 46 , 59 , 60 ], for example, “T-junction” ( Figure 3 d,e), is one of the possible methods to break the bilateral symmetric fluid distribution. Lin Bai also compared the mixing efficiency of “T-junction” with that of the cross section in the same conditions.…”
Section: Micro-mixers Design and Experiments Studymentioning
confidence: 99%